Business cycle synchronization of Tunisia and Euro Zone countries: a parametric and non-parametric analysis - Wissem RABHI (Theoretical and Applied Economics)

(untitled)
In this article, we used a parametric Hamilton approach and a non-parametric Bry- Boschan method to characterize the business cycles of Tunisia and the Euro zone between 1990 and 2017. The estimation results show that Tunisia’s growth cycle is very close to that identified for the Euro zone. Furthermore, based on the transition probability matrix, we find that these coefficients are highly significant and differentiated, ranging from 0.739 to 0.989. Consequently, these probabilities illustrate the state of the Tunisian economy, which is characterized by major recessions. As for the Euro zone economy, the smoothed and filtered probabilities identify five major recessions.